Infliximab trough concentrations during maintenance therapy are associated with endoscopic and histologic healing in ulcerative colitis. Issue 4 (6th December 2017) - Papamichael, K.; Rakowsky, S.; Rivera, C.; Cheifetz, A. S.; Osterman, M. T.
Summary: Background: Endoscopic and histologic healing are emerging as new therapeutic goals in ulcerative colitis (UC), as these endpoints are associated with less relapse, hospitalization and colectomy. Aim: To investigate the association of serum infliximab trough concentrations during maintenance therapy with endoscopic or histologic healing in UC. Methods: In this multi‐center retrospective cohort study, we included consecutive patients with moderate‐to‐severe UC on infliximab maintenance therapy who had an endoscopic evaluation and underwent therapeutic drug monitoring within three months of the colonoscopy, between February 2008 and March 2016. Per event analysis was performed. Endoscopic healing was defined as Mayo endoscopic sub‐score of ≤1. Histologic healing was defined as no or only focal mild active inflammation. Results: Seventy colonoscopies from 56 patients were evaluated. Infliximab trough concentrations (median [interquartile range]) were significantly higher in patients with endoscopic (11.3 [7.6‐14.5] vs 6.3 [0‐9.8] μg/mL, P < .001) or histologic (11.1 [6.7‐14.5] vs 6.7 [0‐9.9] μg/mL, P = .002) healing, respectively, compared to patients without healing. Receiver‐operating characteristic analyses identified infliximab trough concentration thresholds of 7.5 (area under the curve [AUC]: 0.758) and 10.5 (AUC: 0.721) μg/mL to be associated with endoscopic and histologic healing, respectively. Multiple logistic regression analysis identified infliximab trough concentration ≥7.5 ( P = .013; odds ratio [OR]: 4.3; 95% confidence intervals [CI]: 1.4‐13.3) and ≥10.5 μg/mL ( P = .013; OR: 3.8; 95% CI: 1.3‐11) as independent factors associated with endoscopic and histologic healing, respectively. Conclusions: This study demonstrated that infliximab trough concentrations during maintenance therapy are associated with endoscopic and histologic healing in patients with UC. Abstract : Linked Content This article is linked to Lobaton and De Vos and Dutzer et al papers. To view these articles visithttps://doi.org/10.1111/apt.14532 andhttps://doi.org/10.1111/apt.14645 .